2006
DOI: 10.1088/0953-8984/18/19/005
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transitions and conduction properties of superionic, ferroelastic Cu6PS5Br1−xIxsingle crystals (x= 1, 0.75, 0.5, 0.25)

Abstract: The structural origin of Cu + ions conductivity in Cu 6 PS 5 I single crystals is described in terms of structural phase transitions studied by X-ray diffraction, polarizing microscope and Influence of the copper stechiometry on the T c is also discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Recently, we reported a structural PT diagram for this compound based on X-ray diffraction, domain structure observations and calorimetric measurements [18]. The observations under a polarizing microscope did not evidence any domain structure in our samples above T c ¼ ð1442169Þ K. Below T c , the crystal belongs to ferroelastic phase with monoclinic symmetry Cc.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Recently, we reported a structural PT diagram for this compound based on X-ray diffraction, domain structure observations and calorimetric measurements [18]. The observations under a polarizing microscope did not evidence any domain structure in our samples above T c ¼ ð1442169Þ K. Below T c , the crystal belongs to ferroelastic phase with monoclinic symmetry Cc.…”
Section: Introductionmentioning
confidence: 62%
“…This has an influence on the temperature of superionic PT, which varies in the range of 144-169 K for different samples. However, in our previous work [18], we showed that in Cu 6 PS 5 I crystals temperature of the superionic PT is at the same time the temperature of ferroelastic PT T c . Moreover, the temperature of this transition also depends on copper content in the sample.…”
Section: Introductionmentioning
confidence: 70%
“…Copper-and silverbased argyrodites are efficient ionic conductors. However, the ionic conductivity shows a significant dependence on the composition (Beeken et al, 2003(Beeken et al, , 2005Gagor et al, 2006).…”
Section: Commentmentioning
confidence: 99%